Разложите ** множители. 1) (a+b)^(4)−(a−b)^(4)= 2) (x−y3)^(4)−27x+81y= 3)...

0 голосов
64 просмотров

Разложите на множители.
1) (a+b)^(4)−(a−b)^(4)=
2) (x−y3)^(4)−27x+81y=
3) (2x+3y)^(3)+(3x−2y)^(3)=


Алгебра (89 баллов) | 64 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
Разложите на множители.
1) (a+b)^(4)−(a−b)^(4)=(
(a+b)-(a-b))((a+b)+(a-b))((a+b)²+(a-b)²)=2b·2a·2(a²+b²)
=8ab(a²+b²)

2) (x−3y)^(4)−27x+81y=
 (x−3y)^(4)−27(x-3y)=(x-3y)((x−3y)³-3³)=
=(x-3y)(x−3y-3)((x-3y)²+3(x-3y)+9)

3) (2x+3y)^(3)+(3x−2y)^(3)=
=[
 (2x+3y)+(3x−2y)] ·[ (2x+3y)²-(2x+3y)(3x−2y)+(3x−2y)²]=
(5x+y)·(7x²+13xy+19y²)
(80.5k баллов)